Análisis del programa de formación fe-vida en segundo y tercer año de bachillerato de la U.E. Santo Domingo de Guzmán de Gualaceo. - Robles Peralta, Rossana Elizabeth (2015)
The goal of this work is to analyze the formation program faith-life applied for 3 years in the” Saint Dominic School”, with the intention of determining the pertinence of the formative proposal based on the criteria of religious pedagogy and the standards for school religious education proposed by the Ecuadorian Episcopal Conference. The analysis criteria considered are: pedagogic comprehension, doctrinal, methodology, evaluative, school religious teaching and good living. The purpose of the analysis is based on the results and recommendations to improve the teaching training program of formation in faith -life that that applies to the mentioned school.